Education of Noble Morals through Internalization of Honest Attitudes in the Environment Madrasah Ibtidaiyah (MI) - Sukino, Sukino; Kartini, Kartini; Jinani, Syamrotun; Fithri, Zaskia; Nurmaya, Nurmaya (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
Being honest is an important part of achieving success in life in the world and in the hereafter, therefore forming an honest attitude in students from an early age is a priority in noble character education. The purpose of this research is to analyze the internalization process of honest attitude in Madrasah Ibtidaiyah (MI) Mas'udi Pontianak. This study used a qualitative approach, the data collection techniques were carried out through observation, interviews and documentation. The results of this study found that the first internalization of an honest attitude in students begins with providing an understanding of the importance of being honest in life. Educators must provide consistent examples and practices to demonstrate the value and benefits of being honest. Second, the internalization of honest attitude is carried out through three ways that have been consistently carried out, namely through the wise advice method, through the honesty canteen and a series of worship activities at the madrasa. This research provides a clear concept in the process of internalizing honest behavior which is an indicator of strengthening human integrity in social life.